1994
DOI: 10.2186/jjps.38.1005
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Bending Strength in Powder-Liquid VLC Reline Material.

Abstract: The purpose of this study was to investigate the effect on the bending strength of denture base resin relined with REBARON LC and to compare it with other direct relining materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recently, various chemically accelerated and light‐activated polymers have been developed for a hard reline resin that exhibits less tissue irrigation during polymerization. Many investigators examined the flexural strength of denture base polymers and reline polymers ( Hargreaves, 1983; Reitz, Sanders & Levin, 1985; Montes‐G & Draughn, 1986; Wyatt, Harrop & MacEntee, 1986; Bunch, Johnson & Brudvik, 1987; Shlosberg et al ., 1989 ; Hayakawa et al ., 1990 ; Iwahori, 1992), bonding of reline polymer to the denture base polymer ( Arena, Evans & Hilton, 1993; Olvera & de Rijk, 1994; Suzuki et al ., 1994 ; Yasukawa, 1995) water absorption and color change of the new hard reline polymer ( Hayakawa et al ., 1990 ; Arima, Murata & Hamada, 1995). Arima et al (1995) reported the flexural strength of six auto‐polymerizing reline polymers, and they demonstrated that the flexural strength of the resins ranged from 21 to 56 MPa and were lower than those of heat‐cure denture base polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various chemically accelerated and light‐activated polymers have been developed for a hard reline resin that exhibits less tissue irrigation during polymerization. Many investigators examined the flexural strength of denture base polymers and reline polymers ( Hargreaves, 1983; Reitz, Sanders & Levin, 1985; Montes‐G & Draughn, 1986; Wyatt, Harrop & MacEntee, 1986; Bunch, Johnson & Brudvik, 1987; Shlosberg et al ., 1989 ; Hayakawa et al ., 1990 ; Iwahori, 1992), bonding of reline polymer to the denture base polymer ( Arena, Evans & Hilton, 1993; Olvera & de Rijk, 1994; Suzuki et al ., 1994 ; Yasukawa, 1995) water absorption and color change of the new hard reline polymer ( Hayakawa et al ., 1990 ; Arima, Murata & Hamada, 1995). Arima et al (1995) reported the flexural strength of six auto‐polymerizing reline polymers, and they demonstrated that the flexural strength of the resins ranged from 21 to 56 MPa and were lower than those of heat‐cure denture base polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Dentures should be expected to break less readily after reline, as the fit of the dentures to the residual ridge improves and the load becomes better distributed. It has been found, however, that the mechanical strength of reline material is lower than that of the denture base resin, and thus the mechanical strength of the relined denture base may diminish by the influence of the reline material [17,18,35]. Therefore, it is preferable for the reline material to have high mechanical strength.…”
Section: Mechanical Strengthmentioning
confidence: 99%
“…Therefore, it is preferable for the reline material to have high mechanical strength. Many studies on the strength of direct reline materials assess the mechanical strength with bending strength until fracture [18,19,24,35]. However, dentures cannot be used if they become fractured or permanently deformed.…”
Section: Mechanical Strengthmentioning
confidence: 99%